Dynamic covalent polymer networks with mechanical and mechanoresponsive properties reinforced by strong hydrogen bonding. Issue 15 (28th March 2022) - Gao, Wenli; Tang, Rui; Bai, Minghao; Yu, Hengzhe; Ruan, Yonghong; Zheng, Jinli; Chen, Yinjun; Weng, Wengui
Abstract : Mechanoresponsive dynamic covalent networks were designed and synthesized by embedding radical mechanophores into the polymer backbone as crosslinkers. The mechanical properties and mechanoresponsiveness of the polymers were reinforced by hydrogen bonds. Abstract : Dynamic polymer materials with superior mechanical properties and mechanochromism are of great importance for a vast variety of applications including stress sensing, damage detection and soft robots. Herein, mechanoresponsive dynamic covalent polyurethane polymer networks are synthesized by incorporating the 2, 2′-bis(2-phenylindan-l, 3-dione) radically exchangeable mechanophore as the dynamic covalent crosslink and ureidopyrimidinone dimers as the supramolecular crosslink. Due to the mechanically labile nature of the 2, 2′-bis(2-phenylindan-l, 3-dione) crosslink, the polymer materials exhibit mechanochromism. The incorporation of the quadruple hydrogen bonding ureidopyrimidinone motif in the polymer side group leads to the reinforcement of the mechanical properties and mechanochemical responsiveness of the polymers during tensile tests. The polymer materials also exhibit thermal dynamic behaviors, including thermochromism, self-healing and reprocessability, owing to the thermally reversible dissociation and reassociation of 2, 2′-bis(2-phenylindan-l, 3-dione) and the disruption and reformation of ureidopyrimidinone dimers and their stacks.